English pronouncing dictionary - Jones, Daniel; Gimson, A. C.; Ramsaram, Susan (New York : Cambridge University Press, 1991)
In the thirteenth edition. I introduced cortain changes in the phonetic transcription as well as amendments to the pronunciations recorded, with the aim of reflecting more faitfully the currents state of the style of speech on which the dictioanary had traditionally been based. Now, sixty years after the first appearance of the dictionary.
1. The pronunciation model 1.5 The sound oppositions 2. The notation 2.2 Vowels and diphthongs 2.3 Consonants 3. Characteristics of the model 3.1 Vowels and diphthongs
Keywords: ENCICLOPEDIAS Y DICCIONARIOS; DICCIONARIOS DE INGLÉS